Use of genital inspection and female urine tests to detect oestrus in captive Asian elephants - Chatchote Thitaram (2018)
Captive Asian elephant (Elephas maximus) populations are decreasing due to low birth rates compared to wild elephants. Improving oestrous detection in female elephants is required to ensure successful mating in captive and semi-captive herds. Responsive behaviours of eight semi-captive bull elephants to the uro-genital area (genital inspection test) or urinary pheromones (urine test) of 14 female elephants throughout the oestrous cycle were evaluated. Weekly blood samples were collected for 27 consecutive months (14 months for the genital inspection test and 13 months for the urine test) from female elephants to characterize the patterns of circulating progestagen. Responsive behaviours of bulls were compared between females in the follicular versus the luteal phase of the cycle. The sensitivity and specificity of the genital inspection test were 65% and 68%, while those of the urine test were 52% and 61%, respectively. The bulls showed significantly higher "genital inspection", "flehmen from genital area" and "trunk on back" behaviours during the genital inspection test, and "flehmen" behaviours during the urine test in oestrous than in non-oestrous females. In sum, this study showed that monitoring sexual behaviours of Asian elephant bulls towards females or their urine can be used to detect the oestrous period. Although the sensitivity and specificity of both tests were not as high as expected, still, these methods appear to be more efficient at detecting oestrous than traditional methods based on mahout estimations of female receptivity. The use of genital inspection and urine tests may lead to more successful matings and thus to creating self-sustaining populations of captive elephants in range countries. © 2008 Elsevier B.V.